Speaking Skill Assessment Instrument Validity: An Investigation into Instructors’ Perceptions - Alshakhi, Abdullah (Journal of Ecohumanism, 2024)
To EFL learners, speaking the target language with satisfactory fluency is a highly significant aspect of learning the language. Assessment of learners’ progress and achievement in speaking skills is equally significant to identify the course of further action, whether it is for feedback, placement, or grading. At the English Language Institute (ELI), King Abdulaziz University in Saudi Arabia, learners’ proficiency in spoken English is assessed for end-of-the-term grading using Interview and Speaking Project as test instruments. The Interview questions are random, while the Speaking Project involves collection of materials on a chosen topic and report writing, followed by presentation and question-answer session. An empirical research study was conducted to examine ELI teachers’ perceptions on the reliability and validity of the two assessment instruments to accurately measure learners’ proficiency in speaking skill and meeting the requirements to reflect the learning outcomes designed for the speaking English course. The data were collected through a survey questionnaire and a structured interview. The surveyed instructors were also encouraged to express their opinions on the role of formative assessment in determining learners’ final grades in English speaking skill.